Sikap Siswa dan Pemahaman Konsep Matematis dalam Pembelajaran Geometri - Risma Nurul Auliya (SAP (Susunan Artikel Pendidikan), 2019)
The aim of this study was intended to examine the effect of conceptual understanding towards students’ attitude in geometry, and to study how students’ attitude in learning geometry, and to study how students behave in learning geometry. The research utilized a survey method with quantitative approach. This research was conducted at one of junior high school in Rangkasbitung in 2018. The sample consisted of 61 secondary school students in grade 9. A survey instrument was intended to examine students’ attitude in geometry, and essay problems was to measured conceptual understanding ability in mathematics. The data collected was analyzed using linear regression analysis. The result revealed that students’ attitude in geometry was found to be significantly and positively related to conceptual understanding ability. The linear regression analysis estimated the linear regression function to be   Y = 3,214 + 0,725x, where x represented attitude in geometry and Y represented conceptual understanding ability. Furthermore, from the attitude survey it was known that most students enjoy geometry and have a positive attitude that geometry can be used in daily life.